2015
DOI: 10.1088/0967-3334/36/3/531
|View full text |Cite
|
Sign up to set email alerts
|

Changes in heart rate variability and QT variability during the first trimester of pregnancy

Abstract: The risk of new-onset arrhythmia during pregnancy is high, presumably relating to changes in both haemodynamic and cardiac autonomic function. The ability to non-invasively assess an individual's risk of developing arrhythmia during pregnancy would therefore be clinically significant. We aimed to quantify electrocardiographic temporal characteristics during the first trimester of pregnancy and to compare these with non-pregnant controls. Ninety-nine pregnant women and sixty-three non-pregnant women underwent n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 35 publications
(67 reference statements)
2
12
1
Order By: Relevance
“…Our observations of diminished resting HRV (SDNN and RMSSD) with gestation, indicating parasympathetic control blunting, are consistent with previous research (Carpenter et al 2015;Chamchad et al 2007;Lucini et al 1999;Speranza et al 1998). This was matched with a marked reduction in total power, indicating sympathetic dominance (Task Force of the European Society of Cardiology and North American Society of Pacing and Electrophysiology 1996).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our observations of diminished resting HRV (SDNN and RMSSD) with gestation, indicating parasympathetic control blunting, are consistent with previous research (Carpenter et al 2015;Chamchad et al 2007;Lucini et al 1999;Speranza et al 1998). This was matched with a marked reduction in total power, indicating sympathetic dominance (Task Force of the European Society of Cardiology and North American Society of Pacing and Electrophysiology 1996).…”
Section: Discussionsupporting
confidence: 92%
“…The observed reduction in QT interval, the duration of ventricular depolarization and repolarization, with advancing gestation supports previous findings. (Carpenter et al 2015;Carpenter et al 2017a), although the previous studies showed that QT interval was altered as early as the first trimester, these studies agree that ratecorrected QT (QTc) is not altered during pregnancy (Baumert et al 2010). Changes in cardiac time interval in response to exercise were as expected.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations